PROTECTIVE AND CURATIVE EFFECTS OF FRESH ORANGE JUICE (CITRUS SINENSIS L.) SUPPLEMENTATION AGAINST LIVER INJURIES, HEPATIC LIPID, PROTEIN, AND DNAOXIDATIVE DAMAGE INDUCED CYCLOOXYGENASE-2/PROSTAGLANDIN E2 INFLAMMATORY PATHWAY IN FEMALE IRRADIATED RATS - M MORSY, GEHAN; GABAL, ALYAE MS (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Our study aimed to examine the protective and curative ability of fresh orange juice (OJ) (Citrus sinensis L.) to counteract the adverse side effects of ionizing radiation (IR) on hepatic tissues of female irradiated rats and that has not been studied in advance. Methods: Forty-nine adult female Sprague-Dawley albino rats (170±5 g) were divided into four sets of 12 animals, except the healthy control group contained 10 rats only and the irradiated control group contained 15 rats and was divided as follow Group I: Healthy control; Group II: Irradiated control, rats receiving a single dose (20 gray absorbed dose [Gy]) of whole-body γ-rays; Group III: Protective group, rats received (5 ml OJ/kg body weight) once daily for 14 days and after 24 h exposed to irradiation; and Group IV: Curative group, then rats were submitted to irradiation than after 24 h, treated with (5 ml OJ/kg body weight) once every day for 14 successive days. Results: Our results explored that fresh OJ contains significant amounts of antioxidants as flavonoids and polyphenols and consequently pre- or post-fresh OJ supplementation to female irradiated rats attenuated significantly (p≤0.05) hepatic lipid, protein, and DNA-oxidative damage, hepatic inflammation, and activated inflammatory cyclooxygenase-2/prostaglandin E2 pathway, liver fibrosis, impaired liver functions, and hepatic lipid metabolism when compared with irradiated control rats. Furthermore, fresh OJ improved significantly (p≤0.05) the hepatic antioxidant capacity in protective and curative groups in comparison with the irradiated control group. Conclusion: The current research illustrated that fresh OJ may improve and normalize the various hepatic biochemical abnormalities resulted from irradiation due to its high content of active constituents of flavonoids and polyphenols. It is advised for people who exposed to IR, especially females, to consume about (5 ml OJ/kg body weight) before exposure as the most significant improvements were recorded in the protective group that supplemented with OJ before irradiation.